ANALISIS PENDAPATAN USAHA TERNAK SAPI POTONG DI KECAMATAN LETTI KABUPATEN MALUKU BARAT DAYA - Welmince Usmany (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2021)
This research was aimed at studying income level and feasibility of cattle farming in Letti District South West Maluku Regency. The research was conducted on April – May 2020 in three sample villages, namely Batumiau, Laitutun and Desa Tutuwaru. Survey method was applied to thirty cattle herders as respondents, who were chosen through a snow-ball method. Data were both qualitatively and quantitatively collected by applying direct observation and interview through a questionnaire. The results showed that average income of the cattle herders was IDR. 18.616.667 annually with R/C ratio 3.67. It was concluded that the beef cattle farm provided a profit of Rp. 13,552,275,-/ farmer/ year and it is feasible to continue to be developed.